2015
DOI: 10.1016/j.jmb.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Cytoplasmic Regions of KCNH Channels

Abstract: KCNH channels are expressed across a vast phylogenetic and evolutionary spectrum. In humans they function in a wide range of tissues and serve as biomarkers and targets for diseases such as cancer and cardiac arrhythmias. These channels share a general architecture with other voltage-gated ion channels but are distinguished by the presence of an N-terminal Per-Arnt-Sim (PAS) domain and a C-terminal domain with homology to cyclic nucleotide binding domains (referred to as the CNBh domain). Cytosolic regions out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 81 publications
(142 reference statements)
2
44
0
Order By: Relevance
“…These are tetrameric channels that contain large cytoplasmic regions which serve as interfaces for modulatory inputs such as phosphorylation, interaction with kinases, integrins and calmodulin (Cherubini et al, 2005; Morais-Cabral and Robertson, 2015; Schonherr et al, 2000; Sun et al, 2004; Wang et al, 2002; Warmke and Ganetzky, 1994). The cytoplasmic regions include a PAS domain on the N terminus and a domain with homology to cyclic nucleotide binding domains (CNB-homology domain, CNBhD) on the C terminus; it has been shown that the PAS domain and the CNB-homology domain interact with each other (Gustina and Trudeau, 2011; Haitin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These are tetrameric channels that contain large cytoplasmic regions which serve as interfaces for modulatory inputs such as phosphorylation, interaction with kinases, integrins and calmodulin (Cherubini et al, 2005; Morais-Cabral and Robertson, 2015; Schonherr et al, 2000; Sun et al, 2004; Wang et al, 2002; Warmke and Ganetzky, 1994). The cytoplasmic regions include a PAS domain on the N terminus and a domain with homology to cyclic nucleotide binding domains (CNB-homology domain, CNBhD) on the C terminus; it has been shown that the PAS domain and the CNB-homology domain interact with each other (Gustina and Trudeau, 2011; Haitin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-gated ion channels (VGICs) are exquisitely sensitive to transmembrane potential changes by virtue of a voltage-sensor domain that is embedded in the membrane bilayer (Vargas et al, 2012; Yu et al, 2005). Beyond the intrinsic ability to detect transmembrane voltage changes, VGIC superfamily members possess diverse intracellular domains (Yu et al, 2005) that are employed to tune voltage-dependent responses of a particular channel as a consequence of stimuli from signaling molecules (Morais-Cabral and Robertson, 2015; Yang et al, 2015). Although such domains provide a means for chemical cues to influence VGICs, the sensitivity to physical stimuli, such as temperature, in some VGIC superfamily members (Schneider et al, 2014; Vriens et al, 2014), has raised the question about whether there are equivalently specialized domains that can serve as temperature sensors (Bagriantsev et al, 2012; Brauchi et al, 2006; Grandl et al, 2008) or whether thermal responses arise from elements distributed throughout the channel (Chowdhury et al, 2014; Clapham and Miller, 2011).…”
mentioning
confidence: 99%
“…Subsequently, alternate transcripts of KCNH2 in mouse and human heart were shown to encode two subunits: 1a (the original isolate) and 1b (6,7). In the hERG 1b transcript, an alternate 5′ exon replaces 1a exons 1-5, resulting in a shorter, unique N terminus that lacks a Per-Arnt-Sim (PAS) domain (also known as the ether-à-go-go domain) (8,9). In heterologous systems, hERG 1b subunits avidly associate with hERG 1a but fail as homomers to traffic efficiently to the plasma membrane (10).…”
mentioning
confidence: 99%